0107 Differential primary and secondary immune responses in calves fed heat-treated or unheated colostrum. (1st October 2016) - Gelsinger, S. L.; Heinrichs, A. J.
Abstract: An experiment was conducted to compare immune responses between calves that received unheated or heat-treated colostrum. Half of a single, pooled batch of colostrum was frozen without heating; the other half was heated and maintained at 60°C for 60 min before freezing. Bull calves ( n = 26) were randomly assigned to receive 8% of their birth weight as either unheated or heat-treated colostrum. Blood samples were collected at birth and 48 h of age to assess passive transfer. At 14 and 35 d of age, all calves received a subcutaneous injection of 0.2 mg ovalbumin per kg birth weight. Blood was sampled at 0, 4, 8, and 12 h, and daily on days 2 to 10 after each injection. Plasma was collected for analysis of total IgG, ovalbumin-specific IgG, interferon γ (IFNg), tumor necrosis factor α (TNFa), and interleukin 1 β (IL1b). Area under the curve was calculated for plasma cytokine and antibody concentrations, and all data were analyzed using Proc Mixed in SAS. Colostrum treatment, time point, and their interaction were included as fixed effects with calf as a repeated random effect. All calves achieved successful passive transfer of IgG. Calves fed unheated colostrum at birth had greater plasma IL1b and nonovalbumin IgG ( P < 0.05) during the first challenge and tended to have greater nonovalbumin IgG during the second challenge ( P = 0.08). Calves fed heat-treated colostrum at birth tended to have greater plasma IFNg during the second challenge ( P = 0.09). These results imply that calves fed heat-treated colostrum exhibit improved T-cell mediated but reduced innate and B-cell mediated immune response. Despite changes in cytokine and antibody production, neither body weight, body temperature, weekly feed (milk and starter) intake, nor total IgG concentration were different between groups through 45 d of age.